2017
DOI: 10.1186/s40035-017-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of BACE1 in Alzheimer’s synaptic function

Abstract: Alzheimer’s disease (AD) is the most common age-dependent disease of dementia, and there is currently no cure available. This hallmark pathologies of AD are the presence of amyloid plaques and neurofibrillary tangles. Although the exact etiology of AD remains a mystery, studies over the past 30 have shown that abnormal generation or accumulation of β-amyloid peptides (Aβ) is likely to be a predominant early event in AD pathological development. Aβ is generated from amyloid precursor protein (APP) via proteolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 105 publications
(105 reference statements)
2
65
0
Order By: Relevance
“…BACE, also known as beta-site amyloid precursor protein cleaving enzyme, has been implicated in the formation of the Aβ42 peptide found within amyloid plaques [37]. BACE inhibition is known to prevent the production of Aβ in animals and may be a potential therapeutic approach for the treatment of patients with AD [38].…”
Section: Discussionmentioning
confidence: 99%
“…BACE, also known as beta-site amyloid precursor protein cleaving enzyme, has been implicated in the formation of the Aβ42 peptide found within amyloid plaques [37]. BACE inhibition is known to prevent the production of Aβ in animals and may be a potential therapeutic approach for the treatment of patients with AD [38].…”
Section: Discussionmentioning
confidence: 99%
“…32 Moreover, many in vivo studies confirmed that β-secretase play a vital role in AD progression and the use of BACE1 inhibitors improved the neurological function and surpassed the neurological defects imposed in mice of AD model. 33 For example, in a recent study utilizing NB-360 as BACE1 inhibitor in mice with familial Alzheimer disease, the administration of this agent resulted in the enhancement of neuronal activity and the improvement of memory. 34 These effects were attributed to the ability of NB-360 to reduce the formation of Aβ oligomers.…”
Section: Alzheimer's Disease Pathology and Targetsmentioning
confidence: 99%
“…BACE1 is an extensively studied target, due to its potential role in Alzheimer's disease [61]. Indeed, over 300 BACE1 crystal structures were present in the PDB at the time of this challenge.…”
Section: Overview Of Pose Prediction Accuracymentioning
confidence: 99%